Is dental anxiety associated with the behavior of sedated children? - Laércio Alves de AMORIM JÚNIOR; Vinícius Braudes Martins RODRIGUES; Luciane Rezende COSTA; Patrícia CORRÊA-FARIA (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract The aim of this cross-sectional study was to investigate factors associated with dental anxiety in children treated under moderate sedation. Prior to treatment, each child's dental anxiety was evaluated using the modified Venham Picture Test (VPT). Interviews were also conducted with parents/guardians to gather information on the child's dental anxiety (Corah's Dental Anxiety Scale [DAS]), age and sex, shyness or anxiety in the presence of strangers, and dental history, as well as socioeconomic factors. All the children were sedated, and had at least one tooth restored using the atraumatic restorative treatment technique. Child behavior was assessed using the Frankl scale. Data analysis involved descriptive statistics and bivariate tests. The median VPT score was 2.0 (range: 0 to 8). Children who were shy in the presence of strangers (yes: median 2.0 [0-8]; no: 0.5 [0-4]; p = 0.018), and those with negative behavior during dental care (negative: 3.0 [0-8]; positive: 1.0 [0-8]; p = 0.014) had greater anxiety. The child's dental anxiety was associated with the mother's education level (≤ 8 years: 4 [2-7]; > 8 years: 1 [0-8]; p = 0.016). The dental anxiety of children treated under sedation is associated with negative behavior, shyness, and the mother's education level.